If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63a + 65b = 63.55 Solving 63a + 65b = 63.55 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-65b' to each side of the equation. 63a + 65b + -65b = 63.55 + -65b Combine like terms: 65b + -65b = 0 63a + 0 = 63.55 + -65b 63a = 63.55 + -65b Divide each side by '63'. a = 1.008730159 + -1.031746032b Simplifying a = 1.008730159 + -1.031746032b
| lnx=-2.5636 | | f(x)=5sqrt(36+x^2)+4(20-x) | | 6=f+1 | | 6a^2(a-2b)-(a-2b)= | | D^2y+4Dy=8 | | 7=10-j | | 4(-3x+2y)+x(5-Y)= | | (5x+2+Y)5-3x= | | G-4=1 | | y=2x^3+7x^2+7x+2 | | (x-1)(x+8)= | | sin(10*x)=cos(5*x) | | 20-4v=14 | | sinx=0.56 | | M+1=5 | | 0.3x-2.1=5-1.7(x-1) | | 28-2y=8+8y | | 18xsquaredy-12xysquared= | | 6x+3=2x-10 | | 5-h=0 | | -4-5x=-6-6x | | -32-5x=-16-x | | 9x+64=x+56 | | 2=9-(3x-17) | | 9x-80=x+16 | | 10x+40=2x | | 4s+37=133 | | 9+6x=-16x-123 | | 4z-13=-18+9z | | 5t-29=-8+8t | | 3-5x=2x+7 | | 4x^2-6x+5=2 |